Cost‐effectiveness analysis of multiple imaging modalities in diagnosis and follow‐up of intermediate complex cystic renal lesions. (18th March 2021) - Spiesecke, Paul; Reinhold, Thomas; Wehrenberg, Yano; Werner, Sven; Maxeiner, Andreas; Busch, Jonas; Fischer, Thomas; Hamm, Bernd; Lerchbaumer, Markus Herbert
Abstract : Objectives: To compare health‐economic aspects of multiple imaging modalities used to monitor renal cysts, the present study evaluates costs and outcomes of patients with Bosniak IIF and III renal cysts detected and followed‐up by either contrast‐enhanced computed tomography (ceCT), contrast‐enhanced magnetic resonance imaging (ceMRI), or contrast‐enhanced ultrasonography (CEUS). Patients and Methods: A simulation using Markov models was implemented and performed with 10 cycles of 1 year each. Proportionate cohorts were allocated to Markov models by a decision tree processing specific incidences of malignancy and levels of diagnostic performance. Costs of imaging and surgical treatment were investigated using internal data of a European university hospital. Multivariate probabilistic sensitivity analysis was performed to confirm results considering input value uncertainties. Patient outcomes were measured in quality‐adjusted life years (QALY), and costs as averages per patient including costs of imaging and surgical treatment. Results: Compared to the 'gold standard' of ceCT, ceMRI was more effective but also more expensive, with a resulting incremental cost‐effectiveness ratio (ICER) >€70 000 (Euro) per QALY gained. CEUS was dominant compared to ceCT in both Bosniak IIF and III renal cysts in terms of QALYs and costs. Probabilistic sensitivity analysis confirmed these results in the majority of iterations. Conclusion: Both ceMRI and CEUS can be used as alternatives to ceCT in the diagnosis and follow‐up of intermediately complex cystic renal lesions without compromising effectiveness, while CEUS is clearly cost‐effective. The economic results apply to a large university hospital and must be adapted for smaller hospitals.